1997
DOI: 10.1007/bf01904749
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two sampling methods for leafhoppers (Homoptera, Cicadellidae) associated with sesame in the east Mediterranean region of Turkey

Abstract: Yellow sticky-traps and a modified Johnson-Taylor suction-trap were used to index the relative population dynamic Of leafhoppers associated with sesame in the east Mediterranean region of Turkey. Comparison of the obtained results signified important differences between both traps. 32 leafhoppers species were caught in the suction-trap while only 18 species were determined on yellow sticky-traps. For most of the leafhopper species, relatively more males were determined on the yellow-traps than in the suction-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…; Weintraub et al ) and Turkey (Baspinar et al ; Kersting et al . ) but our work has shown that O. orientalis is restricted to the Oriental, eastern Palaearctic and Australian regions. Other recent publications have correctly used O. albicinctus , (e.g.…”
Section: Taxonomymentioning
confidence: 47%
“…; Weintraub et al ) and Turkey (Baspinar et al ; Kersting et al . ) but our work has shown that O. orientalis is restricted to the Oriental, eastern Palaearctic and Australian regions. Other recent publications have correctly used O. albicinctus , (e.g.…”
Section: Taxonomymentioning
confidence: 47%
“…Capturas diferenciales de trampas de pegamento dependiendo del sexo han sido demostradas en cicadélidos (Meyerdirk & Oilfi eld 1985, Kersting & Baspinar 1995, Kersting et al 1997 y en otros hemípteros (Horton 1994). Sin embargo, este efecto no se refl ejó en la posición de las trampas (alta y baja), no siendo signifi cativamente diferente entre machos y hembras (Tabla 2).…”
Section: Resultados Y Discusiónunclassified
“…Esta mayor presencia de machos puede solo estar refl ejando una distinta capacidad de las trampas pegajosas para capturar individuos de distinto sexo de una misma especie (Kersting et al 1997) o bien, a que la relación de sexos favorezca a los machos, principalmente en periodos de verano y otoño (Castle et al 2005), en donde los machos presentan mayor actividad entre plantas en su proceso de búsqueda de hembras para copular, siendo estas últimas, más sedentarias (Teraguchi 1986, Lopes et al 1995, Weintraub & Beanland 2006. Además, la actividad sexual de muchos cicadélidos gravita de acuerdo a las temperaturas mínimas y máximas diarias (Lessio & Alma 2004b, Narhardiyati & Bailey 2005.…”
Section: Resultados Y Discusiónunclassified
“…Previous studies on the population dynamics of O. orientalis outside crop areas indicated that the most suitable leafhopper trapping methods were incandescent light traps and suction traps, with water baffle (similar to yellow pan traps), ultra violet light and pitfall traps less suitable (Osmelak 1987; Osmelak and Fletcher 1988). Suction traps have also been used successfully to monitor low level flight activity of O. orientalis in grasslands (Hosking and Danthanarayana 1988), whereas studies conducted in sesame fields in Turkey showed yellow sticky traps were more effective than suction traps (Kersting et al. 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study have provided important information which can be used to develop more effective disease control strategies for O. orientalis not only in Australia, but also worldwide. Orosius orientalis transmits a range of economically important viruses and phytoplasmas in a variety of crops (Helson 1951; Hutton and Grylls 1956; Harding and Teakle 1985; Osmelak 1986; Kersting et al. 1997).…”
Section: Discussionmentioning
confidence: 99%